A review on mycoprotein: History, nutritional composition, production methods, and health benefits. (March 2022) - Ahmad, Muhammad Ijaz; Farooq, Shahzad; Alhamoud, Yasmin; Li, Chunbao; Zhang, Hui
Abstract: Background: Worldwide, the demand for healthier protein is rapidly increasing due to the population growth and health concerns associated with the consumption of red meat. Animal welfare, disease prevention and environmental challenges are the key driving factors for the development of meat analogues. Mycoprotein is a fungal-derived protein source that has been introduced as a more sustainable and healthier meat alternative due to its fibrous structure and unique functional profile. Scope and approach: In this review, the historical perspective of mycoprotein development, nutritional composition, and the functional properties of mycoprotein are discussed. Next, the extraction of mycoprotein from agro-industrial waste by using different strains of microorganisms via submerged fermentation (SmF), solid-state fermentation (SSF) and surface culture method is summarized. Lastly, the health aspects of mycoprotein consumption including effects on energy intake, appetite regulation, glycemic response, total blood cholesterol, and muscle protein synthesis are also highlighted. Key findings and conclusions: Recent studies have concluded that the mycoprotein has a higher nutritional value, meat-like texture and diverse functional properties which make it a promising source of protein to replace plant-based as well as animal-based meat proteins. By using various microbial strains on a diverse array of substrates under different conditions (pH, temperature, moisture, relative humidity (RH), and inoculum size and age), the extracted biomasses of mycoproteins have shown significantly higher yield and nutritional value via SmF fermentation. Finally, the intake of mycoprotein improves the lipid profile, lowers the energy intake, and stimulates muscle protein synthesis. Highlights: The historical perspective of mycoprotein development is summarized. The nutritional composition and functionality of mycoprotein is discussed. Production methods of mycoprotein from agro-industrial wastes are highlighted. The health benefits of mycoprotein consumption is also reviewed. The major challenges and future perspective of mycoprotein production are also discussed.